2017
DOI: 10.1186/s12913-017-2762-6
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative evaluation of trauma delays in road traffic injury patients in Maringá, Brazil

Abstract: BackgroundRoad traffic injuries (RTIs) are the eighth leading cause of death worldwide, with an estimated 90% of RTIs occurring in low- and middle-income countries (LMICs) like Brazil. There has been minimal research in evaluation of delays in transport of RTI patients to trauma centers in LMICs. The objective of this study is to determine specific causes of delays in prehospital transport of road traffic injury patients to designated trauma centers in Maringá, Brazil.MethodsA qualitative method was used based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Bystander education and awareness has been identified as an important factor influencing this delay, and a qualitative study on trauma delays for patients who had road traffic injury in Brazil found that bystander capacity to provide care was low. 20 Simple interventions at the community level may be highly effective to mobilise first responders in low-resource settings. For example, interventions have included training commercial drivers in providing first aid 21 and training laypeople to be first responders.…”
Section: Discussionmentioning
confidence: 99%
“…Bystander education and awareness has been identified as an important factor influencing this delay, and a qualitative study on trauma delays for patients who had road traffic injury in Brazil found that bystander capacity to provide care was low. 20 Simple interventions at the community level may be highly effective to mobilise first responders in low-resource settings. For example, interventions have included training commercial drivers in providing first aid 21 and training laypeople to be first responders.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Patel and his friends, 4 traffic conditions are the main cause of ambulance delays, followed by bad location and lack of personnel. In a study conducted by Noorani, 10 what influenced ambulance delay are traffic conditions, transportation availability, and distance of travel.…”
Section: Discussionmentioning
confidence: 99%
“…3 Statistics for Road Traffic Injuries (RTIs) also show that an estimated 90% of RTIs occur in low and middle-income countries. 4 Even in Indonesia every 3 hours, there are deaths due to traffic accidents. 5 Trauma patients require immediate medical treatment to improve survival and prevent disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…La literatura científica ha reportado experiencias donde los centros de asistencia y traumatología fueron efectivos en la reducción de las lesiones de AT, basándose en minimizar el tiempo entre la lesión y el tratamiento de reanimación hospitalaria; así, en Francia está basado en el triaje prehospitalario de las víctimas en la escena del accidente a fin de establecer la prioridad en la atención y la inclusión de personal médico entrenado en sus ambulancias para estabilizar al individuo lesionado en el menor tiempo posible 21 . Estudios sobre la atención de emergencias prehospitalarias y AT reportaron barreras que limitan la ejecución de sus intervenciones, las cuales fueron: la ausencia de un sistema integral de servicios médicos de emergencia (SME) entre la capital y el país, la baja calidad en los primeros auxilios brindados, insuficiente entrenamientos sobre respuesta inmediata, recursos inadecuados, demoras en la respuesta de atención y en el traslado a los SME 22 , el involucramiento negativo de ciudadanos, falta de coordinación entre las autoridades, inadecuados servicios prehospitalarios en número y distribución, deficiencias en infraestructura urbana y sistemas de comunicación 23,24,25 . El panel de expertos luego de analizar y contextualizar la evidencia recomendó: establecer una central de emergencia única que pueda derivar la información a las instancias correspondientes, elaborar un protocolo de atención prehospitala-ria con roles definidos para los policías, bomberos, personal de salud, fiscales y ciudadanos, así como la atención en foco con una priorización de víctimas como en accidentes masivos, desarrollar un sistema de educación continua al público que incluya: cómo informar la emergencia (que requisitos mínimos se requiere para poder hacer una llamada útil como, lugar, víctimas, puntos de referencia, y otros datos), concientizar sobre la importancia de la disponibilidad de la vía libre, de despejar esta vía para la circulación de las ambulancias.…”
Section: Intervenciones Centradas En Asistencia Prehospitalariaunclassified